Transcriptome and selected metabolite analyses reveal points of sugar metabolism in the developing leaves of kiwifruit - Huang, Yacheng; Jiang, Kaixiu; Liu, Huanyan; Song, Shuyi; Zhao, Yanmei; He, Bin; Lan, Jixian; Liu, Linya (Frontiers in Plant Science, 2025)
In fruit crops, sugars are essential metabolites, that are produced in leaves and subsequently transported to fruits. However, the sugar levels, gene expression patterns, and sucrose-metabolizing enzyme activities in the leaves of kiwifruit remain poorly understood. In this study, the Illumina NovaSeq 6000 platform was utilized to sequence the kiwifruit leaf transcriptome at 4 developmental stages (A-D), which yielded 109,832 unigenes (mean length, 1135 bp). In addition, the sugar-related genes were compared for their expression profiles and their associations with sugar accumulation and enzyme activities in kiwifruit leaves during growth. The fructose content increased from stages A to C and declined in stage D (mature leaf stage), but the glucose, sucrose, and starch contents increased continuously throughout the leaf development period. The gene expression patterns and sucrose-metabolizing enzyme activities in kiwifruit leaf samples exhibited variations from those of other plant species. Sucrose synthase was revealed as the primary enzyme for sucrose breakdown during early leaf development (stages A and B), whereas cytoplasmic invertase and cell wall invertase exhibited activities comparable to those of vacuolar invertase in the later stages of leaf development (stages C and D), which is consistent with the transcriptional changes noted in most of their encoding genes. On the other hand, sucrose synthase, operating in the synthetic direction, exhibited greater activity than sucrose phosphate synthase across all leaf developmental stages. Overall, these results shed more light on the molecular mechanisms associated with sugar metabolism in kiwifruit leaves.